Investigation on the energy conversion and load control of supercritical circulating fluidized bed boiler units. (August 2018) - Gao, Mingming; Hong, Feng; Liu, Jizhen; Chen, Feng
Highlights: The control model of burning carbon of the supercritical CFB boiler is established. The combustion intensity in the CFB boiler can be monitored. The framework on energy conversion of the supercritical CFB unit has been set up. The designed load control scheme is validated to optimal the control performance in supercritical CFB units. Abstract: Load control is the core of the operation control system on power plant units. The energy conversion process is complicated in the supercritical circulating fluidized bed (SCFB) boiler due to the special fluidized combustion type, which also results in the large thermal inertia. So the control performances of conventional load control scheme without the consideration of carbon storage are poor in SCFB units. To reveal and monitor the energy storage in the boiler, the control model of burning carbon is established. Through the analysis on energy conversion process, the signal of advanced dynamic heat is structured to characterize the variation trend of energy. Based on the combination of the burning carbon control model and the dynamic heat signal, the boiler main control and feed-water control schemes are designed to optimal the control performance. Finally, the verification and application on the 600 MW SCFB unit prove the effectiveness of advanced dynamic heat signal and feasibility of the proposed control scheme.